Hemispheric Imaginations North American Fictions of Latin America - Breinig, Helmbrecht (Re-Mapping the Transnational: A Dartmouth Series in American Studies, 2016)
What image of Latin America have North American fiction writers created, found, or echoed, and how has the prevailing discourse about the region shaped their work? How have their writings contributed to the discursive construction of our southern neighbors, and how has the literature undermined this construction and added layers of complexity that subvert any approach based on stereotypes? Combining American Studies, Canadian Studies, Latin American Studies, and Cultural Theory, Breinig relies on long scholarly experience to answer these and other questions. 'Hemispheric Imaginations', an ambitious interdisciplinary study of literary representations of Latin America as encounters with the other, is among the most extensive such studies to date. It will appeal to a broad range of scholars of American Studies.